The Relationship between Reading Interest and Students' ‎Scientific Literacy in Social Studies subjects - Nimas Puspitasari; Ario Adi Prakoso (JPI: Jurnal Pustaka Indonesia, 2026)
Reading interest is a theoretically relevant factor in students' capacity to access, interpret, and use information for evidence-based reasoning. However, elementary students' scientific literacy remains a persistent concern, particularly in Social Studies learning, where students are expected to connect human-environment issues, social phenomena, and everyday decision-making with empirical evidence. This study aimed to examine the relationship between reading interest and students' scientific literacy in Social Studies learning. A quantitative correlational design was employed involving all 28 fifth-grade students at SD Negeri Genuk 01, West Ungaran District, Semarang Regency, in the 2024/2025 academic year. Data were collected using a reading interest questionnaire and a scientific literacy essay test. The data were analyzed using descriptive statistics, assumption testing, Pearson Product Moment correlation, and coefficient of determination with SPSS. The results showed that students' reading interest was in the good category (M = 73.71), and their scientific literacy was also in the good category (M = 74.52). The correlation analysis indicated a significant positive relationship between reading interest and scientific literacy, r(26) = .724, p < .001, with reading interest explaining 52.4% of the variance in scientific literacy scores. These findings suggest that reading interest is strongly associated with students' scientific literacy in elementary Social Studies, although the correlational design does not permit causal inference. Strengthening school literacy culture, access to meaningful reading materials, and inquiry-oriented reading activities may support students' evidence-based reasoning.